Predation by Coccinellidae on Glycaspis brimblecombei (Hemiptera: Aphalaridae) eggs - Domingues, M. M. [UNESP]; Gêa, B. C. C. [UNESP]; Nascimento, A. C. S.; Queiroz, T. D. S.; Soliman, E. P.; Zauza, E. A. V.; Zonete, M. C. C.; Barbosa, L. R.; Zanuncio, J. C.; Wilcken, C. F. [UNESP] (FapUNIFESP (SciELO), 2025)
Exotic Eucalyptus spp. are the most planted trees species in forest cultivation in Brazil. The red gum lerp psyllid Glycaspis brimblecombei Moore (Hemiptera: Aphalaridae), an invasive exotic pest, reduces the development and wood production of Eucalyptus spp. plantations. The search for natural enemies targeting the egg life stage is beneficial for the integrated pest management of G. brimblecombei. The objective of this work was to test a range of Coccinellidae species that potentially prey on G. brimblecombei eggs. Cycloneda sanguinea Linnaeus, Eriopsis conexa Germar, Harmonia axyridis Pallas, Hippodamia convergens Guerin-Meneville, Jaguarita conjugata Mulsant and Olla v-nigrum Mulsant (Coleoptera: Coccinellidae), reported to be associated with G. brimblecombei infestations, were evaluated. Newly emerged adults of O. v-nigrum and J. conjugata preyed on G. brimblecombei eggs, unlike C. sanguinea, E. conexa, H. axyridis and H. convergens. Predation of eggs by O. v-nigrum was highest, with a mean of 1,016 in 24 hours. These results, evaluating a range of Coccinellidae as predators of G. brimblecombei eggs, confirm the high predation rate of G. brimblecombei eggs by O. v-nigrum and that this ladybug may be important in the integrated management of this pest.